Fiber Optical Network Damage Detection Passive Splitter 1:8 in ODC uses IOT Technology as a means of Real Time Reporting - Asril, Aprinal Adila; Septima, Uzma; Dewi, Ratna; Maria, Popy; Herda, Deri Latika (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
Fiber optic networks currently have a lot of interest, so a network monitoring system is needed that guarantees quality and speed of repair if mass disruption occurs. in research [1] regarding fiber network damage detection using IoT with the use of a 1:4 splitter and the use of a detector that can work at a wavelength of 650nm so that it can detect damaged cables with output in the software. So in connection with this, the author wants to develop the results of this research by using a 1:8 splitter and carrying out detection using the LDR sensor and NodeMCU ESP32 using IoT (Internet of Things) technology. The ESP32 NodeMCU will receive data in the form of light intensity values ??at each ODC from the LDR sensor. And then sent to a database that is connected directly to the Android application. The cable identification process occurs in three states: normal, warning, and error. The test and analysis results show that the hardware device can work well, with attenuation in the passive splitter cable of 10.28 dB and a light source with a wavelength of 650 nm. Cable detected as damaged is indicated by an output in the software with a delay of 4.56 s.